Differences In The Ability To Understand Mathematical Concepts And Problem Solving Of Students Who Are Taught With The Cooperative Learning Model - Desy, Dini Pratiwi (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2022)
This study aims to determine: 1) the difference in the ability to understand mathematical concepts of students who were given the STAD type cooperative learning model with students who were given the CTL learning model; 2) Differences in mathematical problem solving abilities of students who were given the STAD type cooperative learning model with students who were given CTL learning model; 3) the difference in the ability to understand concepts and solve mathematical problems of students who were given the STAD type cooperative learning model with students who were given the CTL learning model; 4)Interaction between STAD and CTL cooperative learning models on students' mathematical problem-solving and conceptual understanding skills This research is a quantitative research with quasi-experimental type. The population is all students of class X MAN 2 Model 2018/2019 school year. The sample in this study was class X IPA-2 as a class taught with the CTL learning model. The data were obtained from the post test with 5 questions for the concept understanding ability test and 5 questions for the students' mathematical problem solving ability test. The data were analyzed descriptively and using the two way ANAVA test technique and continued with the Tuckey test.Based on the results of data analysis and discussion, it was obtained: 1) there were differences in the ability to understand mathematical concepts of students who were given the STAD cooperative learning model and students who were given the CTL learning model; 2) THERE are differences in the ability of solving mathematical problems of students who were given the STAD type cooperative learning model with students who were given the CTL learning model; 3) there are differences ability in solving mathematical concepts and problems of students who were given the STAD type cooperative learning model with students who were given the CTL learning model; 4) there is not significant interaction between the STAD and CTL cooperative learning models on students' mathematical problem-solving and conceptual understanding abilities.